NIMG-54. SPATIAL DISTRIBUTION ATLASES OF POST-TREATMENT MRI SCANS REVEAL DISTINCT HEMISPHERIC DISTRIBUTION OF GLIOBLASTOMA RECURRENCE FROM PSEUDO-PROGRESSION. (5th November 2018) - Ismail, Marwa; Hill, Virginia; Statsevych, Volodymyr; Huang, Raymond; Correa, Ramon; Singh, Gagandeep; Bera, Kaustav; Thawani, Rajat; Madabhushi, Anant; Ahluwalia, Manmeet; Tiwari, Pallavi
Abstract: PURPOSE: A significant challenge in post-treatment assessment of Glioblastoma is differentiating tumor recurrence (TR) from pseudo-progression (PsP), a radiation-induced treatment effect on routine MRI scans. Previous studies on pre-treatment MRI suggested that aggressive GBM lesions are spatially localized in the right hemisphere; and are associated with poor survival. We thus hypothesize that aggressive TR lesions appearing on post-treatment scans, will likely be more localized in the right hemisphere, as compared to benign PsP. METHODS: 106 post-treatment MRI studies (35 PsP, 71 TR) were collected from 2 institutions. Confirmation for PsP and TR was obtained either from pathologic resection or MRI follow-up using RANO criteria. Scans were registered to T1-weighted brain atlas (MNI152), followed by expert delineation of enhancing lesion on Gd-T1w MRI and peri-lesional hyperintensities on T2/FLAIR. Population atlases quantifying the frequency of occurrence of enhancing lesion and peri-lesional hyperintensities were constructed by averaging voxel intensities across all patients. Analysis of differential involvement (ADIFFI) based on a two-tailed Fisher's exact test was performed to compute significant differences (p-value<0.05) across PsP and TR voxels. Significant clusters were finally mapped to a structural atlas to provide anatomic localization of TR and PsP lesions. RESULTS: ADIFFI results showed TR prominence in the right parietal lobe with 75% occurrence in enhancing lesion and 61% in peri-lesional T2/FLAIR hyperintensities. PsP lesions were prominent in the left hemisphere, with peri-lesional T2/FLAIR hyperintensities having a multi-focal spatial distribution in the temporal lobe, insula, and putamen, and enhancing lesion being localized at the temporal lobe. CONCLUSION: TR tends to be lateralized towards the right parietal lobe. PsP tends to be multi-focally distributed in the left hemisphere. Such spatial localization on MRI could serve as a biomarker for differentiating PsP and TR. This could allow for immediate treatment changes in patients with recurrence, while avoiding unnecessary treatment for pseudo-progression.